NARAPIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN UMUM Studi Terhadap Tiga Narapidana Kategori Bandar dan Pengedar di Lapas Kelas IIA Pekanbaru - Riky Novarizal (SISI LAIN REALITA, 2016)
In accordance with the concept of the penal system aims to make inmates as good citizens and responsible in order to return the society and protect the public against the possibility of repeated criminal acts by inmates, as well as the application of the values contained in Pancasila. Under the terms of Act No. 12 of 1995 on Corrections, in particular Article 14 on the rights of prisoners, is the basis that prisoners must be treated humanely in an integrated development system. see how prison officials treat inmates Pekanbaru Class IIA narcotic in the development concept, the condition of the number of inmates in the prisons of narcotics cases dominate Class IIA Pekanbaru either with the category of airports and drug dealers that there needs to be more comprehensive treatment and sustainable. In the researchers used a descriptive method by conducting qualitative research approach, the primary data source is derived from narcotics informant prisoners who are undergoing criminal mass in prisons Class IIA Pekanbaru, to collect data using observation, library research, and in-depth interviews. The method used in empirically includes several things: a research approach data collection techniques and data analysis techniques. Results of the study researchers found the Treatment of Prisoners of narcotics by category airports and dealers be treated the same as inmates cases other crimes both in placement and other treatments, but do differ in health care where current inmates category airports and dealers are experiencing a reaction sakau or hooked in Class IIA Pekanbaru prison which is a common prison. Inmates narcotics by category airports and dealers aware of any specific rules on the treatment of prisoners of narcotic high risk although not implemented in prisons general Pekanbaru Riau, so therefore the behavior of inmates narcotic categories of airports and dealers do agreements informally with officers prisons Class IIA Pekanbaru in addressing compliance their needs .